2022
DOI: 10.1097/pcc.0000000000002883
|View full text |Cite
|
Sign up to set email alerts
|

Direct Discharge to Home From the Pediatric Cardiovascular ICU

Abstract: To describe direct discharge to home from the cardiovascular ICU. DESIGN: Mixed-methods including retrospective Pediatric Cardiac Critical Care Consortium and Pediatric Acute Care Cardiology Collaborative data and survey. SETTING: Tertiary pediatric heart center.PATIENTS: Patients less than 25 years old, with a cardiovascular ICU stay of greater than 24 hours and direct discharge to home from January 1, 2016, to December 8, 2020, were included. Select data describing patients discharged from acute care interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Our findings are generally consistent with other research in adult and pediatric cardiac critical care units. 11,13 Despite the frequency, there is a paucity of data about the risks and outcomes in pediatric patients undergoing DDH. To attempt to better define outcomes for this population, we measured hospital readmission rates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our findings are generally consistent with other research in adult and pediatric cardiac critical care units. 11,13 Despite the frequency, there is a paucity of data about the risks and outcomes in pediatric patients undergoing DDH. To attempt to better define outcomes for this population, we measured hospital readmission rates.…”
Section: Discussionmentioning
confidence: 99%
“…This outcome variable is similar to other studies previously reported on in the pediatric and adult literature. 11,13,18,19 To assess outcomes based on individual patients as opposed to individual admissions, we additionally performed this analysis only utilizing the first admission to the PICU per patient in the study period. We also repeated the analysis after removing patients discharged home with a ventilator, as these patients can have technology dependence best suited for care in an ICU.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An article (12) and editorial (13) on fluid overload, intravascular volume, and fluid removal in the perioperative pediatric cardiac surgery population. A mixed-methods, single-center PC4-registry dataset of outcomes in 364 patients discharged to home directly from the cardiac ICU (14).…”
Section: "Pccm Connections" For Readersmentioning
confidence: 99%